Assistance in integrity zone development for strengthening the public services quality at Sabo Technical Center - Eko Aristanto; Indri Damayanti; Sunarjo Sunarjo; Zaenal Aripin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The development of the integrity zone (ZI) is an effort to maintain integrity as a state civil apparatus in carrying out public services for the community. This activity aims to assist and facilitate performance assessors of the integrity zone (ZI) implementation at the Sabo Technical Center. The implementation of the activity uses two methods, online by using Zoom Meetings and in-person meetings with tutors, technical assistance, and evaluation desks. Carried out effectively for six intermittent working days in September 2021, this activity is located at the Sabo Technical Center, Yogyakarta. The results of the initial evaluation of the implementation of the development of the integrity zone (ZI) on the leveraging component of strengthening public services, for each aspect that becomes the assessment indicator, includes the service standard rate of 85.33; service culture excellence rate of 88.26 and; service satisfaction assessment rate of 91.67. The impact of the implementation of this activity includes increasing implementation team understanding of various regulations that become the harborage of the development of the integrity zone (ZI); governance improvisation of integrity zone (ZI) development documents; improvise infrastructure facilities in public service rooms by meeting the minimum standards set; and presentation improvements on the website owned by the Sabo Technical Center.